2017
DOI: 10.1007/s00276-017-1824-0
|View full text |Cite
|
Sign up to set email alerts
|

Free serratus anterior artery perforator flap: a case report with an anatomic and radiological study

Abstract: Perforator flaps have become very popular in reconstructive surgery. The thoracodorsal and lateral thoracic artery perforator flaps are highly studied, and successful clinical series have been reported, whereas the literature concerning the lateral intercostal and serratus anterior artery perforator flaps is quite poor and their vascular anatomy needs yet to be clarified. We describe a case of free serratus anterior artery perforator flap for the reconstruction of a dorsal defect of the foot, followed by an an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The author attributed this to the radiological protocol used, since the samples had been derived from CT chest angiographies of patients suspected for pneumonic embolism. She believes that a special radiological protocol would have probably revealed more perforators [16], (Table II).…”
Section: Resultsmentioning
confidence: 99%
“…The author attributed this to the radiological protocol used, since the samples had been derived from CT chest angiographies of patients suspected for pneumonic embolism. She believes that a special radiological protocol would have probably revealed more perforators [16], (Table II).…”
Section: Resultsmentioning
confidence: 99%
“…Although Merle et al stated that the use of SAFF as myocutaneous free flap might be impossible due to lack of skin perforators, several authors independently demonstrated direct connections between TDA and intercostal perforators to the skin . Pittet et al (2006) first described boundaries for the harvest of skin islands of myocutaneous SAFF for facial reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, due to its central localisation, the SAFF has a low risk for peripheral arterial vascular disease . Although the exact extent and localisation of perfused skin paddles for myocutaneous SAFF have not been defined so far, the SAFF has been successfully used as a myocutaneous free flap for the reconstruction of the face, the head and neck or the lower limb …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proportion of branched samples should be clearer about arteries in that muscle (1,6). Serratus anterior muscle flaps have not been widely studied, particularly in Vietnam (7)(8)(9)(10). The vascular branches entering the serratus anterior muscle are often varied regarding quantum and origin; additional data on this aspect are needed if these differences are clinically significant.…”
Section: Introductionmentioning
confidence: 99%